UPAYA MENINGKATAN KEHIDUPAN DOA KELUARGA MELALUI MODEL KATEKESE BIBLIS DI KBG MARIA BINTANG TIMUR PAROKI STA. MARIA PEMBANTU ABADI WERI - Benedikta T. Henakin; Elisabeth A. I. Da Santo; Waltrudis S. Naibae (JOURNAL OF COMMUNITY DEDICATION, 2026)
This Community Service Program (PKM) was implemented with the aim of improving the quality of family prayer life through the application of the biblical catechesis model in the KBG Maria Bintang Timur, Sta. Maria Pembantu Abadi Weri Parish. The main problem identified was the low level of family prayer habits and the congregation’s limited understanding of the importance of prayer as part of the Christian faith. To address these issues, a biblical catechesis approach was used, focusing on the Scriptures as the primary basis for faith reflection. The program was implemented through pastoral care that included deepening the Word of God, faith dialogue, reflection on life experiences, and formulating concrete actions within the family. The results of the program showed an increase in the congregation’s understanding of family prayer and a growing awareness to practice prayer together more regularly. Thus, the biblical catechesis model was deemed effective in strengthening the spiritual life of families at the church-based community level.